Solutions by everydaycalculation.com

How to solve 2x + 1 = 3x + 2? Get the answer and stepwise instruction to solve linear equation in one variable 𝒙.

We have 2**x** + 1 = 3**x** + 2

First, we move the * x* terms to the LHS and constant terms to the RHS of the equation, inverting the sign on the terms. This is also called transposing method.

Transposition is a faster method and combines the following two steps, were we to solve the equation by:

i) Subtracting 1 from both sides

ii) Subtracting 3**x** from both sides

Therefore, 2**x** - 3**x** = 2 - 1

or, -**x** = 1

Next, divide both sides by -1, which is the coefficent of **x**

-1**x**-1 = 1-1

**x** = 1-1 or, **x** = -1

© everydaycalculation.com